Local stage dependent necessity of radiation therapy in rhabdoid tumors of the kidney (RTK) - Melchior, Patrick; Dzierma, Yvonne; Rübe, Christian; Graf, Norbert; Kager, Leo; Dieckmann, Karin; Kroiss, Sabine; Hubertus, Jochen; Warmann, Steven; Schenk, Jens-Peter; Leuschner, Ivo; Nemes, Karolina; et al. (International journal of radiation oncology, biology, physics, 2020)
Purpose: Rhabdoid tumor of the kidney (RTK) is one of the most aggressive childhood renal tumors. Overall survival ranges from 22% to 47%. The indication for radiation therapy (RT) in usually very young patients is an ongoing discussion. Recent protocols recommend RT independent of local stage, the latter being a good discriminator in other childhood kidney tumors. In this study, we analyze the evidence for RT in regard to risk factors, including tumor stage. Methods and Materials: This study analyzed 58 patients with RTK from Austria, Switzerland, and Germany treated in the framework of 4 consecutive, prospective renal/rhabdoid tumor studies from 1991 to 2014. All treatment protocols included multimodality treatment, including high-intensity chemotherapy, surgery, and RT. Results: Local stage distribution was not applicable, I, II, and III in 1, 6,11, and 40, respectively. Twenty-nine (50%) patients had stage IV disease at diagnosis. Thirty-seven patients (64%) achieved complete remission, and 49% (18/37) relapsed. Thirty-four patients (60%) patients had progressive disease and died, 17 had local disease, 10 had combined disease, and 7 had distant disease; 2 treatment-related deaths were reported (3%). Twenty-one patients received RT during first-line treatment, 18 of them to all involved sites. Eight of the 34 cases of progressive disease occurred in irradiated patients. The local failure rate of treated patients with local stage II or III disease was 29% (6/18) in patients irradiated to all sites compared with 68% (15/22) in nonirradiated patients. One of 6 stage I patients received RT, and 1 patient experienced distant relapse (2-year progression-free and overall survival both 83% +/- 15%). Progression-free survival for local stage II and III disease treated with RT, adjusted for early relapse or treatment abandonment, was 67% +/- 11%, compared with 15% +/- 7% without RT (P < .0001). Conclusion: The 68% local failure rate in nonirradiated patients underlines the importance of local treatment. Our experience supports the use of RT for local control in higher stage disease. In contrast, no local relapse in 6 local stage I patients, including 5 nonirradiated patients, suggests omission of RT in this favorable subset of usually infant patients with RTK. (C) 2020 Elsevier Inc. All rights reserved.
Gesehen am 14.12.2020